INTEGRATED CORPORATE STRUCTURES UNDER TRANSITION ECONOMY: COMPLIANCE WITH THE WORLD STANDARDS OF LEGAL AND ECONOMIC PRACTICE - Zyatkovskyi, Ihor (Journal of European Economy, 2018)
By analyzing the organizational and methodological principles and financial aspects of establishing integrated corporate structures in Ukraine, the author determines the degree of compliance of the domestic version of business groups organization with the world practice, as well as discusses the drawbacks of the legal basis for creation of the given structures.